The Implementation of Block Craft 3D As the Realization of SDGs 2030: Design Media in An Attempt to Improve Spatial Capabilities Student - Al Hasani, Salma Zahrotun Nihayah; Zuroidah, Ninik (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2023)
Low mathematical spatial reasoning is identified as a problem for students learning mathematics. In Indonesia, students' mathematical spatial reasoning is still rated as medium to low, according to theoretical analyses of several research findings. To enhance students' mathematical spatial reasoning on three-dimensional spatial geometry material, this study will evaluate the efficacy of STEAM-based mathematics learning using Block Craft 3D application learning media. The steps in research and development (R&D) using the ADDIE model are: (1) analyzing the need for media development; (2) designing media concepts; (3) realizing the media design that has been made; (4) attempting to determine whether the media made is suitable for its intended use; and (5) evaluating by measuring the achievement of media development goals. The research results indicated that STEAM-based learning with Block Craft 3D media would positively impact mathematics learning by enhancing students' spatial abilities on geometry content